Tatak Pilipino [episode no. 22] [videorecording]. ([Quezon City ABS-CBN], 1991)
A unique display of Pilipino ways and style.
Contents: Pera gimmick (10 min.) -- 100 Most significant Filipinos of the 20th century (in 3 pts.) -- Mangkukulam (15 min.) -- Halo-halo (5 min.) -- Arnis (10 min.).
Credits: Hosts, Jim Paredes and Gel Santos Relos.
Keywords: Money -- Philippines; Arnis; Desserts -- Philippines; Magic -- Philippines; Witchcraft -- Philippines; Philippines -- Biography; Sociology; Home economics; Human kinetics